The importance of physical education in preschool age. - Akhunov Umidbek Ruzibaevich (Global Scientific Publishing, 2024)
This article discusses the role of physical education and the processes of its implementation in the development of the younger generation, which is the future of our country, into mentally and spiritually perfect people
Keywords: personality; education; quality